High Performance Liquid Chromatographic and Biological Studies of 2-[(4-Methyl-2-nitrophenyl)azo]-3-oxo-N-phenylbutanamide (Yellow Pigment) - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2010)
A simple reverse phase high performance liquid chromatographic (HPLC) method was developed for the quantitative determination of 4-methyl-2-nitroaniline (MNA) a potential reduction product of 2-[(4-methyl-2-nitrophenyl)azo]-3-oxo-N-phenylbutanamide (pigment yellow 1, PYI). Quantifications were carried out by Integrations of the peak areas using internal standardization method with N-(2.4-dichlorobenzoyl)aniline (DCBZA) as an internal standard The proposed dye (PY1) and its potential reduction product. 4-methyl-2-nitroaniline (MNA) arid the internal standard were separated by a reverse phase El PLC system The dye was then incubated with NADH to Investigate its possible reduction into the corresponding primary amine (MNA). However, no reduction was observed. The proposed compound was also incubated with rat microsomal preparations fortified with NADPH In both experiments, compounds in the incubates were extracted into dichloromethane (DCM) and finally evaporated under nitrogene. No metabolic reduction to MNA was observed as well. This indicates the in vitro stability of PYI and hence safety of the dye in tuns of potential toxicity from this reduction produet.
Keywords: Azo dyes; In vitro metabolism; Printing inks; Am reduction; 2-[(4-Methyl-2-nitrophenyl)azo]-3-oxo-N-phenylbutanamide; HPLC; AZO DYES; REDUCTION; PRODUCTS